2015
DOI: 10.1111/jopr.12344
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation and Patient Satisfaction of Single Zirconia‐Based and High‐Noble Alloy Porcelain‐Fused‐to‐Metal Crowns in the Esthetic Area: A Retrospective Cohort Study

Abstract: The results of the study showed that a high survival rate could be achieved in both ZC and HC groups. Chipping of the veneering porcelain was the most frequently seen event that led to short-term (less than 3 years) failure and complications. The patients' rating of ZC crowns was not superior to HC crowns. Well-designed studies with high evidence level and large sample size are still needed to further explore the clinical success of ZC and HC crowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…It has been recommended that patient satisfaction should be included in the final evaluation even if such assessment is subjective. 16,17 In summary of the present study, the patient satisfaction (VAS) was relatively high (>80) in all three groups. This indicated that all three treatment strategies were acceptable for patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been recommended that patient satisfaction should be included in the final evaluation even if such assessment is subjective. 16,17 In summary of the present study, the patient satisfaction (VAS) was relatively high (>80) in all three groups. This indicated that all three treatment strategies were acceptable for patients.…”
Section: Discussionsupporting
confidence: 53%
“…In recent years, psychosocial parameters relate to patient's perception of implant therapy have gained considerable interests. It has been recommended that patient satisfaction should be included in the final evaluation even if such assessment is subjective . In summary of the present study, the patient satisfaction (VAS) was relatively high (>80) in all three groups.…”
Section: Discussionsupporting
confidence: 50%
“…It is recommended that general dental practitioners consider adopting minimally invasive techniques in the first instance before moving on to more invasive treatment plans. Indirect restorations require more tooth preparation and more than one appointment to be completed [17][18][19][20]. Metal ceramic restorations though they have shown long-term success due to good mechanical properties [21], achieving a natural appearance is more challenging with a metal-ceramic restoration than an all-ceramic restoration due to the fact that metal copings prevent light transmission [22].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, achieving a natural appearance is more challenging with a metal-ceramic restoration than an all-ceramic restoration due tothe fact that metal copings prevent light transmission. 3,4 This has led to an increase in the use of non-metallic restorations such as zirconia-based restorations.…”
Section: Introductionmentioning
confidence: 99%